PENGARUH PENGALAMAN PRAKTIK KERJA INDUSTRI, INFORMASI DUNIA KERJA DAN MOTIVASI KERJA TERHADAP KESIAPAN KERJA SISWA SMK NEGERI SE-KOTA SERANG - Agia Seriana Yusadinata, - (2022)
Penelitian ini bertujuan untuk mengetahui pengaruh pengalaman praktik kerja industri, informasi dunia kerja dan motivasi kerja terhadap kesiapan kerja siswa kelas XII program keahlian otomatisasi tata kelola perkantoran SMK Negeri se-kota Serang. Populasi dalam penelitian ini adalah siswa kelas XII program keahlian otomatisasi tata kelola perkantoran di SMK Negeri se-kota Serang sebanyak 434 siswa dengan ukuran sampel sebanyak 208 siswa. Metode penelitian yang digunakan adalah metode Explanatory Survey dengan teknik pengumpulan data menggunakan kuesioner. Pengolahan data menggunakan teknik analisis data regresi linier berganda dengan bantuan program IBM SPSS for Windows 25.0. Hasil penelitian menunjukkan bahwa gambaran umum tentang pengalaman praktik kerja industri, informasi dunia kerja, motivasi kerja dan kesiapan kerja siswa kelas XII program keahlian otomatisasi tata kelola perkantoran SMK Negeri se-kota Serang termasuk kedalam kategori tinggi. Pengalaman praktik kerja industri, informasi dunia kerja dan motivasi kerja memiliki kontribusi pengaruh terhadap kesiapan kerja siswa sebesar 56,10%. Simpulan dalam penelitian ini adalah terdapat pengaruh yang positif dan signifikan antara pengalaman praktik kerja industri, informasi dunia kerja dan motivasi kerja terhadap kesiapan kerja siswa baik secara parsial maupun simultan. Kata Kunci : Pengalaman praktik kerja industri, Informasi dunia kerja, Motivasi Kerja siswa dan kesiapan kerja ABSTRACT The Effect Of Industrial Work Practice Experience, Information On The World Of Work And Work Motivation On The Work Readiness Of Students At State Vocational Schools Throughout The City Of Serang. by Agia Seriana Yusadinata This study aims to determine the effect of industrial work practice experience, information on the world of work and motivation to enter the world of work on the work readiness of class XII students in the automation program for office governance at State Vocational Schools throughout the city of Serang. The population in this study was class XII students of the office management automation expertise program at State Vocational Schools throughout the city of Serang as many as 434 students with a total sample of 208 students. The research method used is the Explanatory Survey method with data collection techniques using questionnaires. Data processing using multiple linear regression data analysis techniques with the help of the IBM SPSS for Windows 25.0 program. The results showed that the general description of the experience of industrial work practices, information on the world of work, motivation to enter the world of work and work readiness of class XII students of the automation skill program for office management at State Vocational Schools throughout the city of Serang belonged to the high category. Experience of industrial work practices, information on the world of work and work motivation have an influence contribution to students' work readiness by 56.10%. The conclusion in this study is that there is a positive and significant influence between industrial work practice experience, information on the world of work and work motivation on students' work readiness, either partially or simultaneously. Key Words: The experience of industrial work practices, Information on the world of work, Work motivation and Work readiness